PENGARUH INVESTASI PADA SEKTOR PERHUBUNGAN DARAT DAN LAUT DI KABUPATEN JENEPONTO SULAWESI SELATAN - Maksud Hakim (Jurnal Ilmiah Econosains, 2013)
Absract This study aimed to determine the effect of investment on land and marine transportation sector in Jeneponto. This study described the influence of determinant factors (population and GDP) on the amount of investment in transportation sector, particularly in the land and marine transportation for five year period, from 2008 until 2012. Based on data it was found that GDP grew year by year in that period due to higher value of the product that produced by Jeneponto people as well as the economic stability and certainty in that region, while Jeneponto population also grew 0.8% annually. Those two factors significantly influenced the investment value in transportation sector, especially land and marine transportation. Those variables also found to be strong correlated, with more than 90% of variations in investment variables explained by GDP and population growth.